Assessing the building maintenance culture for old shop house in Jonker Street, Malacca / Iqbal Ariff Shahar - Shahar, Iqbal Ariff (2014)
This dissertation will discuss about the maintenance culture among the old shop houses owners in Jonker Street, Malacca. In chapter one, author will introduce the background of study for this dissertation. Other than that, the author will state the problem statement for this dissertation, the aim and objective of this dissertation and scope of study for this dissertation. Other than that, this chapter also will state the methodology of study for this dissertation. In chapter 2, author will explain in literature review about the old shop houses and maintenance. This will include the definition of terminology for building maintenance. Other than that, the author will explain more on the history of old shop house and its definition. This chapter also will discuss on the maintenance nature, maintenance classification and maintenance planned for the old shop houses. For chapter 3, the author will briefly discuss on the research methodology for this dissertation. It will include methods of data collections, background of cased study place and history of development on the cased study place. This chapter also will summarize on flow of research for this dissertation. Chapter 4 in this dissertation will discuss on the results and findings that has been collected and analyzed by the author. The author has analyzed the result based on the information that has been gathered from the questionnaire and interview session conducted by the authors. The respondents for this dissertation consist from the old shop houses owners and tenants and the officers in Majlis Bandaraya Melaka Bersejarah (MBMB). Every analysis by the author will include the findings to ensure its meet the objectives that have been stated before. Last but not least, in chapter 5, the author has concluded all the analysis and findings from the research whether it will meet the objectives of the research or not. Thischapter also will discuss the objectives based on the findings by the author.